Functional Magnetic Resonance in the Evaluation of Oesophageal Motility Disorders - Francesco Covotta; Luca Piretta; Danilo Badiali; Andrea Laghi; Tommaso Biondi; Enrico S. Corazziari; Valeria Panebianco (Gastroenterology Research and Practice)
Functional magnetic resonance imaging (fMRI) has been recently proposed for the evaluation of the esophagus. Our aim is to assess the role of fMRI as a technique to assess morphological and functional parameters of the esophagus in patients with esophageal motor disorders and in healthy controls. Subsequently, we assessed the diagnostic efficiency of fMRI in comparison to videofluoroscopic and manometric findings in the investigation of patients with esophageal motor disorders. Considering that fMRI was shown to offer valuable information on bolus transit and on the caliber of the esophagus, variations of these two parameters in the different types of esophageal motor alterations have been assessed. fMRI, compared to manometry and videofluoroscopy, showed that a deranged or absent peristalsis is significantly associated with slower transit time and with increased esophageal diameter. Although further studies are needed, fMRI represents a promising noninvasive technique for the integrated functional and morphological evaluation of esophageal motility disorders.